Prevalência do negociado sobre o legislado e a necessária adequação da estrutura sindical - Morais, Juliana Ferreira de (2025)
This paper analyzes freedom of association as an essential prerequisite for overcoming the structural crisis faced by Brazilian trade unionism. Based on the premise that representativeness — understood as the effective ability to defend workers’ interests — can only be fully exercised in contexts of genuine freedom of association, the study examines how the hybrid model adopted by the 1988 Federal Constitution still preserves remnants of the corporatist regime, which hinder the full autonomy of trade unions. This discussion becomes particularly relevant in light of the expansion of the unions’ bargaining powers, consolidated by the Labor Reform, which established the prevalence of collective bargaining over statutory law, including for the restriction of rights. In this scenario, the research questions whether Brazilian trade unionism possesses the representativeness and legitimacy necessary to effectively exercise these expanded prerogatives. Finally, the study proposes adjustments to the Brazilian trade union system, including the amendment of Article 8 of the Constitution, as a means of strengthening freedom of association, collective autonomy, and legal certainty in labor relations, including within the context of transnational enterprises.